2021
DOI: 10.3389/fmars.2021.749070
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitivity of the Bacterial Pigment Cycloprodigiosin Enables Settlement in Coral Larvae—Light as an Understudied Environmental Factor

Abstract: The survival of coral reefs largely depends among other factors on the recruitment of a new generation of coral individuals that are more adapted to a rapidly changing climate and other anthropogenic stressors (e.g., pollution, sedimentation). Therefore, a better understanding of the coral settlement process, the molecules involved as well as crucial environmental drivers that control settlement success are needed. In this study, we identified a novel settlement inducer for the brooding scleractinian coral Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…However, the ecological relevance of sublethal effects of such morphological changes in planulae are yet to be demonstrated [ 52 ]. Compared to other acute coral larvae toxicity studies [ 67 , 87 , 88 ], which used a period of 24 h to investigate settlement in A. tenuis planulae, we chose a test duration of 48 h. This was due to the circumstance that for the species we tested, a 24 h period was insufficient to achieve ≥70% settlement (metamorphosis and attachment) within the negative control (data not shown), which is in agreement with previous settlement studies [ 73 , 89 , 90 ]. Thus, a test duration of 48 h is considered appropriate for the assessment of both investigated endpoints.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, the ecological relevance of sublethal effects of such morphological changes in planulae are yet to be demonstrated [ 52 ]. Compared to other acute coral larvae toxicity studies [ 67 , 87 , 88 ], which used a period of 24 h to investigate settlement in A. tenuis planulae, we chose a test duration of 48 h. This was due to the circumstance that for the species we tested, a 24 h period was insufficient to achieve ≥70% settlement (metamorphosis and attachment) within the negative control (data not shown), which is in agreement with previous settlement studies [ 73 , 89 , 90 ]. Thus, a test duration of 48 h is considered appropriate for the assessment of both investigated endpoints.…”
Section: Discussionsupporting
confidence: 80%
“…Due to the described potential complications using live CCA in settlement assays, we suggest the consideration of alternative settlement cues for the development of a standardized coral toxicity test. Petersen et al [ 89 ] recently identified the morphogenic red pigment cycloprodigiosin, produced by the CCA-associated marine bacterium Pseudoalteromonas rubra #1783 [ 90 ], as a potent chemical cue to induce full settlement (metamorphosis and attachment) in L. purpurea planula larvae at reliably high success rates of nearly 90% after 48 h in combination with an alternating 12 h dark and light cycle. Applying such an isolated chemical cue would be ideal in toxicity assays, as it may counteract secondary effects, as well as compound loss caused by interactions of CCA with the media and/or target compound, and to assure optimized reliability and replicability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pigments were identified from Serratia marcescens and reported to be produced within a select temperature range . A variety of bacterial genera including Pseudoalteromonas are known to produce prodigiosin and derivatives. , Recently, cycloprodigiosin was also demonstrated as a compound involved in the attachment and settlement of coral Leptastrea purpurea larvae . Thus, a broad range of biological activities are reported for prodiginines.…”
Section: Resultsmentioning
confidence: 99%
“…45,47 Recently, cycloprodigiosin was also demonstrated as a compound involved in the attachment and settlement of coral Leptastrea purpurea larvae. 48 Thus, a broad range of biological activities are reported for prodiginines. In our study, features at m/z_t R 324.207_12.1 min and 322.191_11.1 min were identified via GNPS library matches to prodigiosin and cycloprodigiosin, respectively (Figure 6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%